The disassembly line balancing and modeling - McGovern, Seamus; Gupta, Surendra M.; Penn, Michael; Sinha, Priyanka; McGraw-Hill eBooks (New York : McGraw-Hill, 2011)
"The definitive guide to The disassembly line: balancing and modeling provides in-depth information on this complex process essential to remanufacturing, recycling, and environmentally conscious manufacturing. This pioneering work offers efficient techniques required to solve problems involving the number of workstations required and the disassembly sequencing of end-of-life products on the disassembly line. In this book, the disassembly line balancing problem (DLBP) is described, defined mathematically, and illustrated by case studies. Combinatorial optimization methodologies are presented as solutions to the DLBP. This authoritative volume also covers product planning, line and facility design, sequencing and scheduling, inventory, just in time, revenue, and unbalanced lines"--provided by publisher.
"This unique resource comprehensively covers the disassembly line--a key component of remanufacturing, recycling, and environmentally conscious manufacturing, as well as reverse and closed-loop supply chains"--provided by publisher.
Part I. Disassembly background -- Part II. Disassembly-line balancing -- Part III. Further disassembly-line considerations.
Print version c2011.
Includes index.
Also issued in print and PDF versions.
Description based on cover image and table of contents, viewed on July 18, 2011.
Keywords: Assembly-line methods; Resource recovery facilities; Recycling (Waste, etc.); Electronic books